2022
DOI: 10.1111/idh.12566
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the success rate of pit and fissure sealants on first molars: 12 months follow‐up study

Abstract: Cleaning of pits and fissures of occlusal surface of the posterior teeth are difficult because of their anatomy. Despite oral hygiene measures and the delivery of local fluoride, the occlusal surfaces of teeth cannot be adequately cleaned by most children and their parents, and this increase the risk of dental caries. 1 The anatomical fissures of teeth are the most susceptible areas to dental caries initiation, which directly depends on the fissures' shape and depth.Dental caries rarely occurs on smooth surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Behroozian et al used Feigal's criterion [ 12 ] to evaluate the treatment failure rate by analyzing three factors: marginal adaptation, marginal discoloration, and anatomical shape of permanent first molars treated with pit and fissure sealants. After 12 months, they observed that the success rate was 74.3% and with this, the authors emphasized that pit sealants are a valid therapy for the prevention of tooth decay [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Behroozian et al used Feigal's criterion [ 12 ] to evaluate the treatment failure rate by analyzing three factors: marginal adaptation, marginal discoloration, and anatomical shape of permanent first molars treated with pit and fissure sealants. After 12 months, they observed that the success rate was 74.3% and with this, the authors emphasized that pit sealants are a valid therapy for the prevention of tooth decay [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve treatment efficacy, some care must be taken, such as application technique, which must be careful to avoid humidity, because the presence of saliva can prevent the penetration of resinous fluid into the microporosities, decrease shear strength, and increase microleakage, these being the main causes of failure and failure of preventive treatment [ 5 , 11 , [13] , [14] , [15] ].…”
Section: Introductionmentioning
confidence: 99%
“…The total failure rate of fissure sealants after one year was 27.7%. The most frequent reason for the failure of fissure sealants was marginal discoloration [11]. The efficiency of fissure sealing in preventing caries is related to the quality of the sealed fissure, as incompletely sealed fissures were more susceptible to caries development than completely sealed fissures [12].…”
Section: Introductionmentioning
confidence: 99%
“…Caries prevention is essential because caries can cause problems with speech, appearance, and psychology, as well as abnormal tongue habits and masticatory defects [ 4 ]. Therefore, the use of pit and fissure sealants, which can both treat and prevent early enamel caries, is widely accepted as a popular preventive therapy for dental caries [ 5 ].…”
Section: Introductionmentioning
confidence: 99%